Unlocking English proficiency: Youtube's impact on speaking skills among indonesian university students - Akhmad Habibi; Mailizar Mailizar; Lalu Nurul Yaqin; Turki Mesfer Alqahtani; Mukhlash Abrar; Budianto Hamuddin; Failasofah Failasofah (Journal of Technology and Science Education, 2024)
This study examines the factors affecting the intention to use and actual use of YouTube in improving English-speaking skills in Indonesia. To meet the aims, we extended the theory of technology acceptance model (TAM); two external factors, subjective norms, and perceived enjoyment, to support the TAM variables (perceived ease of use, perceived usefulness, attitude, intention to use, and actual use). Data were collected through a survey with 526 measurable responses from Indonesian preservice English teachers in three Indonesian universities. The data were analyzed through partial least square structural equation modeling (PLS-SEM), measurement, and structural model. The findings informed that all hypothesized relationships were accepted and confirmed. The strongest relationship emerged between intention to use and actual use. Meanwhile, the weakest correlation was between subjective norms and perceived ease of use. The study facilitates recommendations for future researchers, language educators, and all related parties.